COVID-19 in Asia law and policy contexts - Ramraj, Victor Vridar 1968- (New York, NY Oxford University Press, 2020)
This is a book for an extraordinary time, about a pandemic for which there is no modern precedent. It is an edited collection of original essays on Asia's legal and policy responses to the COVID-19 pandemic, which, in a matter of months swept around the globe, infecting millions. It transformed daily life in almost every corner of the planet-from the empty streets of once-bustling Mumbai to the silent 2020 Olympic Games venues of Tokyo. In a matter of weeks, the unimaginable became ordinary: lockdowns of cities and entire countries, physical distancing and quarantines, travel restrictions and border controls, movement-tracking technology, mandatory closures of all but essential services, economic devastation and mass unemployment, and government assistance programs on record-breaking scales. Yet a pandemic on this scale, under contemporary conditions of globalization, has left governments and their advisors scrambling to improvise solutions, often themselves unprecedented in modern times, such as the initial lockdown of Wuhan. This collection of essays analyzes law and policy responses across Asia, identifying cross-cutting themes and challenges. It taps the collective knowledge of an interdisciplinary team of sixty-one researchers both in the service of policy development, and with the goal of establishing a scholarly baseline for research after the storm has passed. The collection begins with an epidemiological overview and survey of the law and policy themes. This jurisdiction-specific case studies and cross-cutting thematic essays cover five topics: first wave containment measures; emergency powers; technology, science, and expertise; politics, religion, and governance; and economy, climate, and sustainability"--
Introduction and background -- A short history and thematic overview / Victor V. Ramraj & Matthew Little -- China : community policing, high-tech surveillance, and authoritarian durability / Feng Xu & Qian Liu -- Taiwan : democracy, technology and civil society / Wen-Chen Chang & Chun-Yuan Lin -- Vietnam : marshalling state and non-state actors / Cuong Nguyen & Thanh Phan -- Spread of information versus spread of virus : China, Taiwan, and Hong Kong / Guoguang Wu -- Borders and entry controls in Asia / Jaclyn L. Neo & Darius Lee -- Central banks and their limits in a pandemic / Christian Hofmann -- Governing through / Contagion Lynette J. Chua & Jack Jin Gary Lee -- Pandemics and emergency powers in Asia / Victor V. Ramraj & Arun K. Thiruvengadam -- Japan : keeping the death toll to the minimum / Tomoya Ono & Shigenori Matsui -- Thailand : emergency responses or more social turbulence? / Rawin Leelapatana & Chompunoot Tangthavorn -- India : federalism, majoritarian nationalism, the vulnerable and marginalized / Reeta Chowdhari Tremblay & Namitha George -- International health regulation and compliance / Susan Carolyn Breau & Preethi Lolaksha Nagaveni -- Can technology and privacy co-exist in a pandemic? / Ze Shi Li, Visakha Phusamruat, Tony Clear, & Daniela Damian -- Singapore : technocracy and transition / Maartje De Visser & Paulin Straughan -- South Korea : democracy, innovation, and surveillance / Sunghee Chung & Sujin Lee -- Hong Kong : the healthcare professions and the outbreak / Calvin W.L. Ho & Daisy Cheung -- Religion amid the pandemic : a Buddhist case study / Benjamin Schonthal & Tilak Jayatilake -- Bhutan : the role of the constitutional monarch in a public health crisis / Sonam Tshering & Nima Dorji -- Cambodia : public health, economic, and political dimension / Sratana Ly, Vandanet Hing, & Kimsan Soy -- Indonesia's response to the pandemic : too little, too late? / Nadirsyah Hosen and Nurussyariah Hammado -- Malaysia : improvised pandemic policies and democratic regression / Azmil Tayeb & Por Heong Hong -- Myanmar : pandemic in a time of transition / Kai Ostwald & Tun Myint -- Sri Lanka : pandemic-catalysed democratic backsliding / Bhavani Fonseka, Luwie Ganeshathasan, & Asanga Welikala -- Governments and business / Tan Cheng Han & Jiangyu Wang -- Nationalism, consolidation and rationalization in the aviation industry / Jae Woon Lee & MichelleDy -- Asian trade and supply chain linkages / Philip Calvert & Dan Ciuriak -- Mongolia : after successful containment, challenges remain / Charles Krusekopf & Mendee Jargalsaikhan -- Reset or revert in the new climate normal / Navraj Singh Ghaleigh & Louise Burrows -- Southeast Asian workers in a just-in-time pandemic / Helen Lansdowne & James Lawson.
Includes index.
Keywords: Communicable diseases -- Electronic books -- Asia; Medical policy -- Asia; Public health laws -- Asia; COVID-19 (Disease) -- Law and legislation -- Asia; COVID-19 (Disease) -- Social aspects -- Asia